Pengetahuan Ibu Menyusui dalam Pemberian ASI Ekslusif Bayi di Lingkungan Prioritas Stunting - Taufik Ismail; Yunarti Yunarti; Sri Meiyenti (Aceh Anthropological Journal, 2023)
This study describes how knowledge related to exclusive breastfeeding in Nagari Kampung Baru Korong Nan Ampek. Proper exclusive breastfeeding will minimize the occurrence of stunting. The exclusive breastfeeding coverage rate in Nagari is quite low at 40%. This study aims to examine why the coverage rate of exclusive breastfeeding in Nagari is still low and how the knowledge of mothers who have babies is related to exclusive breastfeeding. This study uses qualitative research methods with data collection techniques through observation, in-depth interviews, literature study and documentation. In the selection of informants using a purposive sampling technique, where the informants were selected by researchers, namely mothers who were breastfeeding their children during the exclusive breastfeeding period, starting from 0 to 6 months of age. Based on the results of the study, it was found that the knowledge of mothers who have babies is still in a low stage, there are still many mothers who do not exclusively breastfeed their babies, mothers in Nagari still give other foods besides breast milk in the age range of 0 to 6 months. The low coverage of exclusive breastfeeding in Nagari is influenced by several factors such as cultural factors, socialization from the government, education and social environmental factors. Mother's knowledge regarding exclusive breastfeeding in this nagari has not yet reached the stage of correct giving practice. Mothers do not know about exclusive breastfeeding because in their culture there is also no such thing.Abstrak: Penelitian ini mendeskripsikan bagaimana pengetahuan terkait ASI eksklusif di Nagari Kampung Baru Korong Nan Ampek. Pemberian ASI eksklusif yang tepat akan meminimalisir terjadinya stunting. Angka cakupan ASI eksklusif di Nagari cukup rendah yaitu 40%. Penelitian ini bertujuan untuk mengkaji mengapa angka cakupan pemberian ASI eksklusif di Nagari masih rendah dan bagaimana hubungan pengetahuan ibu yang memiliki bayi dengan pemberian ASI eksklusif. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, studi literatur dan dokumentasi. Dalam pemilihan informan menggunakan teknik purposive sampling, dimana informan dipilih oleh peneliti yaitu ibu yang sedang menyusui anaknya pada masa pemberian ASI eksklusif mulai dari usia 0 sampai dengan 6 bulan. Berdasarkan hasil penelitian diketahui bahwa pengetahuan ibu yang memiliki bayi masih rendah, masih banyak ibu yang tidak memberikan ASI eksklusif pada bayinya, ibu di Nagari masih memberikan makanan lain selain ASI pada bayinya. rentang usia 0 sampai 6 bulan. Rendahnya cakupan ASI eksklusif di Nagari dipengaruhi oleh beberapa faktor seperti faktor budaya, sosialisasi dari pemerintah, pendidikan dan faktor lingkungan sosial. Pengetahuan ibu tentang ASI eksklusif di nagari ini belum sampai pada tahap praktik pemberian yang benar. Ibu tidak tahu tentang ASI eksklusif karena di budaya mereka juga tidak ada yang seperti itu.